[Strengthening prevention and health promotion in and for old age]. - Gellert, Paul; Brandenburg, Hermann; Franke, Annette; Kessler, Eva Marie; Krupp, Sonja; Pantel, Johannes; Schramek, Renate; Simm, Andreas; Swoboda, Walter; Wurm, Susanne; Fuellen, Georg (Zeitschrift für Gerontologie und Geriatrie, 2024)
BACKGROUND: Disease prevention and health promotion in and for old age have become increasingly more important. Nevertheless, more (national) research and implementation in practice is needed, as the international comparison shows. OBJECTIVE: To develop guiding principles for research and practice on prevention and health promotion in and for old age. MATERIAL AND METHODS: As part of an iterative process, members of the German Society of Gerontology and Geriatrics came together in workshops and symposia to formulate key guiding principles and fields of action for prevention and health promotion. RESULTS: The following were worked out: 1) prevention and health promotion are useful and possible up to oldest age, 2) prevention and health promotion for advanced age should start early, 3) prevention and health promotion must take into account the diversity and heterogeneity of the life situations of old people, 4) prevention and health promotion promote and demand self-determination and participation, 5) prevention of multiple illnesses must be given greater attention, 6) prevention of the need for long-term care and prevention in long-term care must be treated equally, 7) prevention and health promotion must be thought of in terms of life worlds and across sectors, paying particular attention to aspects of social inequality and a focus on resources, 8) prevention and health promotion and the related research must be interdisciplinary and transdisciplinary and be applied at different levels, from molecular to societal. DISCUSSION: The guiding principles outline the focal points of future-oriented ageing, health and healthcare research and open up fields of action but also show the limits of this approach for political decision-makers, researchers and practitioners.
EVALuna2:562720